Peningkatan Minat Berwirausaha Remaja Ipnu Kalimade Kesesi Melalui Pelatihan Penggunaan Shopee Affiliates - M. Shofi Anshori; Teguh Wijoyo; Intania Assai Nissa Sahiba; Fadhli Muhtazam; Hendri Hermawan Adinugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
This research is in-depth about efforts to increase the entrepreneurial interest of IPNU Kalimade Kesesi teenagers by implementing training on the use of Shopee Affiliates. The training method includes an in-depth understanding of affiliate marketing concepts, practices for using the Shopee Affiliates platform, and effective product marketing strategies in the online realm. The research subjects were IPNU Kalimade Kesesi teenagers who were actively involved in learning and training activities. Data was collected through surveys, observations and interviews to gain an in-depth understanding of changes in entrepreneurial interests and skills after training. In this research, the research team used the Participatory Action Research (PAR) method to provide training and mentoring to IPNU Kalimade Kesesi teenagers in an effort to increase interest in entrepreneurship. The research results show a significant increase in teenagers' knowledge, skills and interest in entrepreneurship after attending Shopee Affiliates training. The results of this research include that they can take advantage of opportunities from the potential of the digital economy and increase their online marketing skills, their contribution regarding their interest in entrepreneurship is very successful so that they really want to learn about Shopee Affiliates, Shopee Affiliate and increase their practical skills in digital marketing, and increase their self-confidence. those who are new to starting their own business journey. The implications of this research are not only limited to the educational sphere, but can also be a reference for the government, non-profit organizations and industry players in supporting the development of youth entrepreneurship. Keywords: Interest in Entrepreneurship, IPNU Youth in Kalimade Kesesi Village, Use of Shopee Affiliates, Entrepreneurship Education.